Cribiform-morular variant of papillary thyroid carcinoma and familial adenomatous polyposis: Report of a case - Giuffrida, Mario; De Giorgi, Federica; Cozzani, Federico; Bonati, Elena; Del Rio, Paolo (Acta Biomedica Atenei Parmensis, 2021)
Cribiform-morular thyroid carcinoma is a rare variant of papillary thyroid carcinoma. It is usually related to Familial Adenomatous Polyposis (FAP) but rarely it may be sporadic. This variant of PTC occurs in young females and it is rare in the elderly. We report a case of a 20 years old female presenting thyroid carcinoma and personal history of FAP.